Do modernismo em William Faulkner : «As I Lay Dying» - Azevedo, Carlos (2014)
This article offers a reading of As I Lay Dying which takes into account the historical and cultural context of William Faulkner’s narrative fiction. The focus is both on the author’s tendency to see his fiction as shadowed by the repressed myths and stories of his (Southern, Victorian) culture and on the refracted techniques of Modernism, to which he was introduced as a young man. As this study attempts to demonstrate, it was by linking the classic Southern romance with the modern sense of experimental form, by merging a deep-seated sense of regional history with an awareness of the fracture of historical time, that Faulkner became a major novelist, drawn to write in a way that was as old as storytelling and, at the time, as new as Cubism. As a matter of fact, it is in the works of the end of the Twenties and Thirties, after having invented Yoknapatawpha County as a fictional setting for his fiction, that we can feel the writer’s experimental power at full force, for example in The Sound and the Fury (1929) and As I Lay Dying (1930). The latter is discussed as the story of the funeral journey of a clan of poor whites, which is told through fifty-nine interior monologues, reflections on living and dying, a moving wagon, and the complex and grotesque panorama of life surrounding it. This paper also argues for Addie Bundren as the absent presence in the novel, a mother and wife who obsesses the other members of the family, someone who tends to exist for her creator outside the coventional parameters of language. After having systematized Addie’s dichotomy between words and deeds and its projection on the ‘streamof-consciousness’ of the Bundrens, a more detailed analysis of the main characters’ thoughts, actions and language is undertaken, while the mother’s soliloquy is explored as a 'provincial' (i.e., from the Yoknapatawpha province) version of a modernist manifesto.